Respuesta :
Answer:
y = 2
x = 7
Explanation:
- 5x + 3y = 41
- 3x - 6y = 9
Make the coefficient of "y" in equation 1 same
{ 5x + 3y = 41 } * 2 → 10x + 6y = 82 ........equation 1
→ 3x - 6y = 9 ........equation 2
solving them using linear combination
- 10x + 6y = 82
- 3x - 6y = 9
============
- 13x = 91
- x = 7
Find y:
- 5x + 3y = 41
- 5(7) + 3y = 41
- 3y = 41 - 35
- 3y = 6
- y = 2
5x+3y = 41 multiply whole thing by -2 so the y’s cancel out
3x-6y = 9
Becomes
-10-6y=-82
- subtract
3x-6y = 9
=
-13x+0y=-91
X=7
Plug in x to find y
3(7)-6y=9
21-6y=9
Y=2
3x-6y = 9
Becomes
-10-6y=-82
- subtract
3x-6y = 9
=
-13x+0y=-91
X=7
Plug in x to find y
3(7)-6y=9
21-6y=9
Y=2